2022
DOI: 10.1111/iej.13872
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of partial and full pulpotomy in cariously exposed mature molars with symptoms indicative of irreversible pulpitis: A randomized controlled trial

Abstract: Aim The aim of this study was to assess and compare the clinical and radiographic outcome of partial pulpotomy and full pulpotomy using Biodentine in cariously exposed mature molar teeth with symptoms indicative of irreversible pulpitis. Methodology This study is an unicentric, double‐arm, randomized superiority clinical trial with parallel experimental groups, registered under CTRI (CTRI/2019/12/022559). Fifty mature permanent molar teeth with carious exposures with symptoms indicative of irreversible pulpiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
1
28
2
Order By: Relevance
“…Both capping materials exhibited high and comparable successful outcomes, 89.2% for MTA Angelus and 82.5% for Total Fill BC with no significant differences between them. These results are in accordance with previous findings for ProRoot MTA by Taha and Khazali (2017) and Biodentine by Jassal et al (2023) who described successful outcomes in 85% and 88% in similar cases, respectively. However, such percentages are higher compared to those mentioned by Careddu and Duncan (2021) and Baranwal et al (2022) who reported a successful outcome in the percentage range of 78% to 80% for Biodentine in cases of irreversible pulpitis.…”
Section: Discussionsupporting
confidence: 93%
“…Both capping materials exhibited high and comparable successful outcomes, 89.2% for MTA Angelus and 82.5% for Total Fill BC with no significant differences between them. These results are in accordance with previous findings for ProRoot MTA by Taha and Khazali (2017) and Biodentine by Jassal et al (2023) who described successful outcomes in 85% and 88% in similar cases, respectively. However, such percentages are higher compared to those mentioned by Careddu and Duncan (2021) and Baranwal et al (2022) who reported a successful outcome in the percentage range of 78% to 80% for Biodentine in cases of irreversible pulpitis.…”
Section: Discussionsupporting
confidence: 93%
“…However, partial pulpotomy preserves more tooth structure, and the presence of some coronal pulp can help to facilitate pulp testing during post‐operative reviews and potentially provide more clarity during the determination of the outcome of treatment. To date, there are three studies comparing the outcomes of partial and full pulpotomy (Asgary et al, 2018; Baranwal et al, 2022; Jassal et al, 2022). Although full pulpotomy seemed to perform better than partial pulpotomy the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the hierarchy of evidence, randomized clinical trials are the gold standard for comparison of treatment procedures. A randomized clinical trial compared the outcome of full pulpotomy and partial pulpotomy in management of irreversible pulpitis using Biodentine and considered 10 min as a cut‐off point for achieving haemostasis using 2.5% NaOCl 77 . Similarly, Ramani et al .…”
Section: Outcome Of Partial Pulpotomy In Teeth With Irreversible Pulp...mentioning
confidence: 99%